Hubungan Pengetahuan Anemia dan Pola Menstruasi dengan Kadar Hemoglobin Pada Remaja Putri di SMA Negeri I Ende - Maria Camelia T.Bupu; Linda Dewanti; Ivon Diah Wittiarika (Universitas Malahayati, 2024)
ABSTRACT Anemia is a condition where there is a decrease in the number of erythrocytes as indicated by a decrease in hemoglobin levels, hematocrit and the number of erythrocytes. The incidence of anemia in adolescent girls in developing countries is around 53.7%, anemia often attacks adolescent girls due to stress, menstruation, or late eating (WHO, 2018). Data from the NTT Provincial Health Office in 2022, the coverage of adolescent girls who received anemia status (hemoglobin) screening services was 32.7%. In 2023, in the first quarter, the number of teenage girls in grades 7 and 10 who were identified as anemic was 38.1%. From the results of the screening at the high school level, the Ende District Health Service in 2022 stated that in Ende there were 38% of female students at risk of anemia.To determine the relationship between knowledge of anemia and menstrual patterns in adolescent girls with hemoglobin levels at SMA Negeri I Ende. This research is an observational analytical research with a cross-sectional approach. The sample of this study was 246 teenagers aged 15-16 years who met the inclusion and exclusion criteria. There is a significant relationship between knowledge about anemia and menstrual patterns in young women (p value 0.05) with hemoglobin levels at SMA Negeri I Ende. There is a significant relationship between knowledge of anemia and menstrual patterns in adolescent girls and hemoglobin levels at SMA Negeri I. Keywords: Knowledge of Anemia, Menstrual Patterns, State High School 1 Ende ABSTRAK Anemia adalah keadaan dimana terjadi penurunan jumlah masa eritrosit yang ditunjukkan oleh penurunan kadar hemoglobin, hematokrit dan hitung eritrosit. Angka kejadian anemia pada remaja putri di Negara- negara berkembang sekitar 53,7%, anemia sering menyerang remaja putri disebabkan karena keadaan stress, haid, atau terlambat makan (WHO, 2018). Data dari Dinkes Propinsi NTT pada tahun 2022 cakupan remaja putri yang menerima layanan pemeriksaan status anemia (hemoglobin) sebesar 32,7% . Pada tahun 2023 triwulan I jumlah remaja putri kelas 7 dan 10 yang teridentifikasi anemia sebanyak 38,1 %. Dari hasil penjaringan tingkat SLTA Dinas Kesehatan Kabupaten Ende tahun 2022 menyatakan bahwa di Ende terdapat 38 % siswi mengalami resiko anemia. Mengetahui hubungan pengetahuan anemia dan pola menstruasi pada remaja putri dengan Kadar hemoglobin di SMA Negeri I Ende. Penelitian ini merupakan penelitian analitik observasional dengan pendekatan cross sectional. Sampel dari penelitian ini adalah 246 remaja umur 15-16 tahun yang memenuhi kriteria inklusi dan eksklusi. Ada hubungan yang signifikan pengetahuan tentang anemia dan pola menstruasi pada remaja putri (p value 0,05) dengan dengan kadar Hemoglobin di SMA Negeri I Ende. terdapat hubungan yang signifikan antara pengetahuan anemia dan pola menstruasi pada remaja putri dengan kadar hemoglobin di SMA Negeri I Ende. Kata Kunci: Pengetahuan Anemia, Pola Menstruasi, SMA Negeri I Ende